How do some nurses achieve post-traumatic growth in stressful situations? Analysis of the role of hope, meaning of life, and resilience with the mediating role of coping self-efficacy - Majid Yousefi Afrashteh; Masoumeh Moradi; Leila Rahmandel (Heliyon)
Background: This study aimed to investigate the relationship between hope, the meaning of life, resilience, and post-traumatic growth (PTG), with coping self-efficacy as a mediating factor among nurses working in COVID-19 care departments. Methods: This was a quantitative cross-sectional study involving 263 nurses from three university hospitals in Zanjan, Iran, in 2022. Data were collected using Connor and Davidson's Resilience Questionnaire, Schneider's Hope scale, Steger's Meaning in Life questionnaire, Tedeschi and Calhoun's PTG inventory, and Chesney's coping self-efficacy scale. Data were analyzed using SPSS-26 and LISREL-10.2 software. Results: Path analysis was used to analyze the causal model, which demonstrated a good fit with the data., the results showed. The results revealed direct and significant effects of resilience (ƿ<0.05, β = 0.14), hope (ƿ<0.05), β = 0.16), the meaning of life (ƿ<0.05, β = 0.13), and coping self-efficacy (ƿ<0.05, β = 0.20) on PTG among nurses. Additionally, the mediation of coping self-efficacy in the relationship between resilience, hope, meaning of life, and PTG in nurses was confirmed through the analysis of multiple mediators. Conclusion: The study revealed that the combination of resilience, hope, and the meaning of life, mediated by coping self-efficacy, has significant predictive power for PTG in nurses.